Safety, pharmacokinetics, and pharmacodynamics of ART‐648, a PDE4 inhibitor in healthy subjects: A randomized, placebo‐controlled phase I study - Akira Tanaka; Hiroshi Nagabukuro; Kanako Kuniyeda; Haruhi Ando; Toshinori Higashi; Hirokazu Wakuda; Naoyuki Otani; Hideo Kudo; Masae Kuranari; Hidetoshi Furuie; Naoto Uemura (Wiley, 2024)
Abstract Phosphodiesterase 4 (PDE4) inhibitor is associated with a broad‐spectrum anti‐inflammatory mechanism. However, securing clinically efficacious doses with sufficient safety margins remains challenging due to class specific adverse events that are often unavoidable in the clinic. ART‐648 is an orally available PDE4 inhibitor being developed for the treatment of inflammatory diseases. According to the estimated clinical doses based on an in vitro whole‐blood assay, a phase I study was designed. The purpose of this phase I study was to assess the safety, tolerability, pharmacokinetics (PK), and pharmacodynamics (PD) following single and multiple administration of ART‐648 in healthy subjects. PD was assessed by suppression of lipopolysaccharide‐induced TNFα release in ex vivo whole‐blood assay. In the single rising dose study, ART‐648 was safe and well tolerated with a dose‐proportional increase in exposures up to 4 mg. Single doses of ART‐648 demonstrated dose‐dependent PD response, indicating target engagement at 2‐8 mg doses. In the multiple rising dose study, doses up to 4 mg BID after careful titration were well tolerated, while doses up to 6 mg BID were tolerated not in all but the majority of subjects. In conclusion, ART‐648 exhibits a favorable PK profile with robust target engagement at clinically safe and tolerated doses identified in healthy subjects.